Propranolol reduces implicit negative racial bias - Terbeck, Sylvia (Springer-Verlag, 2012)
BACKGROUND: Implicit negative attitudes towards other races are important in certain kinds of prejudicial social behaviour. Emotional mechanisms are thought to be involved in mediating implicit “outgroup” bias but there is little evidence concerning the underlying neurobiology. The aim of the present study was to examine the role of noradrenergic mechanisms in the generation of implicit racial attitudes. METHODS: Healthy volunteers (n = 36) of white ethnic origin, received a single oral dose of the β-adrenoceptor antagonist, propranolol (40 mg), in a randomised, double-blind, parallel group, placebo-controlled, design. Participants completed an explicit measure of prejudice and the racial implicit association test (IAT), 1–2 h after propranolol administration. RESULTS: Relative to placebo, propranolol significantly lowered heart rate and abolished implicit racial bias, without affecting the measure of explicit racial prejudice. Propranolol did not affect subjective mood. CONCLUSIONS: Our results indicate that β-adrenoceptors play a role in the expression of implicit racial attitudes suggesting that noradrenaline-related emotional mechanisms may mediate negative racial bias. Our findings may also have practical importance given that propranolol is a widely used drug. However, further studies will be needed to examine whether a similar effect can be demonstrated in the course of clinical treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00213-012-2657-5) contains supplementary material, which is available to authorized users.